Kajian Literatur: Sikap Penyangkalan (Parental Denial) sebagai Hambatan Pencarian Bantuan Profesional pada Gangguan Kesehatan Mental Anak - Tri Setyo Wardhani (Jurnal Ilmu Sosial dan Humaniora, 2026)
Mental health disorders among children have become an increasing public health concern in Indonesia, yet many affected children do not receive timely professional mental health services. One of the major barriers is parental denial, in which parents fail to recognize, minimize, or reject their child’s mental health problems, leading to delayed help-seeking. This literature review aimed to analyze the role of parental denial as a barrier to professional help-seeking for children with mental health disorders in Indonesia. A literature search was conducted using PubMed, Scopus, ScienceDirect, SpringerLink, ProQuest, and Google Scholar for articles published between 2017 and 2024. The findings revealed that parental denial is influenced by multiple factors, including limited mental health literacy, stigma toward mental illness, emotional responses, collectivist cultural values, family beliefs, and reliance on traditional or non-medical treatment. These factors contribute to delayed recognition of mental health problems, postponement of professional consultation, and limited access to evidence-based interventions. The reviewed literature suggests that improving parental mental health literacy, reducing stigma, and implementing culturally sensitive interventions through collaboration among families, schools, healthcare providers, and communities are essential to promote early help-seeking and improve children's access to appropriate mental health services in Indonesia.